"We see you" – Sawubona, safe spaces and being human together in South Africa: An ethnographic probe into a fresh expression of church - Nell, Ian (HTS teologiese studies, 2019)
Since the end of apartheid and the advent of democratic elections, South Africa has made great strides, but we still continue, at times, to be unable to practise sawubona. On one level, this is not surprising given our history of separateness. The article asks whether fresh expressions of church, such as the community supper at St Peters in Mowbray, Cape Town, indeed create a space for genuinely ‘seeing’ each other and practicing being human together. The article also explores some of the problems inherent in ethnographic work amongst the poor and the vulnerable by asking whether some types of ethnographic work actually practice a form of epistemic violence and muses upon the idea of the postcolonial gaze and ‘othering’ in ethnography in contexts of poverty in the global South. Can ethnography, in some cases, be a form of academic pornography?